Pengaruh Kompensasi dan Motivasi terhadap Kinerja Pegawai - Fachrezi, Farhan Rifa; Prasetiyo, Budi (Penerbit Goodwood, 2024)
Purpose: To determine the influence of improvement and motivation on the performance of Diskominfotik employees in the West Bandung Regency. Research methodology: The research instrument uses a questionnaire, the research method uses descriptive and associative methods, the application uses SPSS 25, and the survey used in this study uses a method of distributing questionnaires via Google Forms. Results: The results show that Compensation and motivation affect employee performance by 53.4%. Limitations: The variables estimated to have a relationship with the dependent variable are only connected in the conceptual framework of this study. Therefore, this conceptual framework does not include variables that may not have been included. Contribution: This study provides an overview of the West Bandung Regency Diskominfotik in making policies in terms of resolution and motivation.